A maximum efficiency point tracking control method for ultrasonic motors with temperature compensation - Lei Zhao; Chunchen Cai; Xuefei Mao; Dengyun Wu; Jiyang Zhang; Zhuoming Yu; Ying Feng (IET Electric Power Applications, 2023)
Abstract To compensate for the influence of temperature on the efficiency of an ultrasonic motor (USM), this paper proposed a maximum efficiency point tracking control method for temperature drift by analysing the relationships between the maximum efficiency point and the voltage and frequency of the driving circuit. The method first calculates the frequency update step of the driving circuit by the polynomial surface fitting method, considers the influence of temperature rise on the voltage‐efficiency‐frequency characteristics, and then adjusts the frequency in real time to compensate for temperature effects. Simulation and experimental results show that our method can improve the USM performance at the maximum efficiency point under changing temperature. Maximum efficiency point tracking algorithm with temperature compensation algorithm achieves maximum efficiency in experiment.